Association of Sleep Quality with Anxiety and Depression Symptoms among Computer Science Students - Soares Passos, Lígia Maria; Murphy, Christian; Chen, Rita Zhen; Santana, Marcos Gonçalves; Passos, Giselle Soares (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP), 2023)
The mental health of undergraduate students is becoming a growing concern, with recent studies showing that students in STEM fields such as Computer Science (CS) are most at risk of exhibiting symptoms of anxiety and depression. However, to date there has been little work in understanding the causes of these symptoms. This paper presents the results of a study of 146 undergraduate CS students at a public university in Brazil, in which students' sleep characteristics and symptoms of depression and anxiety were assessed using validated questionnaires. The results demonstrate that 61.0% of CS students reported poor sleep quality, and that 21.9% and 33.6% of CS students were in the clinical anxiety and clinical depression groups, respectively. These results are not unrelated: CS students with poor sleep quality were 6.08 times more likely to be in the clinical anxiety group and were 4.35 times more likely to be in the clinical depression group than CS students with good sleep quality.